In situ evaluation of anticancer drug methotrexate-DNA interaction using a DNA-electrochemical biosensor and AFM characterization - Rodrigues Pontinha, Ana Dora; Alves Jorge, Sonia Maria [UNESP]; Paquim, Ana-Maria Chiorcea; Diculescu, Victor Constantin; Oliveira-Brett, Ana Maria (Royal Soc Chemistry, 2011)
An in situ evaluation of the dsDNA-methotrexate (MTX) interaction was performed by voltammetry using a DNA-electrochemical biosensor and characterized by atomic force microscopy (AFM) at a highly oriented pyrolytic graphite (HOPG) surface. Electrochemical experiments in incubated solutions showed that the interaction of MTX with dsDNA leads to modifications to the dsDNA structure in a time-dependent manner. The AFM images show reorganization of the DNA self-assembled network on the surface of the HOPG electrode upon binding methotrexate and the formation of a more densely packed and slightly thicker MTX-dsDNA lattice with a large number of aggregates embedded into the network film. The intercalation of MTX between complementary base pairs of dsDNA lead to the increase of purine oxidation peaks due to the unwinding of the dsDNA. The dsDNA-electrochemical biosensor and the purinic homo-polynucleotide single stranded sequences of guanosine and adenosine, poly[G] and poly[A]-electrochemical biosensors, were used to investigate and understand the interaction between MTX and dsDNA.